Data from: Response of moose hunters to predation following wolf return in Sweden - Wikenros, Camilla; Sand, Håkan; Bergström, Roger; Liberg, Olof; Chapron, Guillaume (Dryad, 2015)
Background: Predation and hunter harvest constitute the main mortality factors affecting the size and dynamics of many exploited populations. The re-colonization by wolves (Canis lupus) of the Scandinavian Peninsula may therefore substantially reduce hunter harvest of moose (Alces alces), the main prey of wolves. Methodology/Principal findings: We examined possible effects of wolf presence on hunter harvest in areas where we had data before and after wolf establishment (n = 25), and in additional areas that had been continuously exposed to wolf predation during at least ten years (n = 43). There was a general reduction in the total number of moose harvested (n = 31,827) during the ten year study period in all areas irrespective of presence of wolves or not. However, the reduction in hunter harvest was stronger within wolf territories compared to control areas without wolves. The reduction in harvest was larger in small (500-800 km2) compared to large (1,200-1,800 km2) wolf territories. In areas with newly established wolf territories moose management appeared to be adaptive with regard to both managers (hunting quotas) and to hunters (actual harvest). In these areas an instant reduction in moose harvest over-compensated the estimated number of moose killed annually by wolves and the composition of the hunted animals changed towards a lower proportion of adult females. Conclusions/Significance: We show that the re-colonization of wolves may result in an almost instant functional response by another large predator—humans—that reduced the potential for a direct numerical effect on the density of wolves’ main prey, the moose. Because most of the worlds’ habitat that will be available for future colonization by large predators are likely to be strongly influenced by humans, human behavioural responses may constitute a key trait that govern the impact of large predators on their prey. harvest_and_quotasIncludes data of harvest quotas and number of harvested moose.